El cambio climático en el ártico: Más allá del Círculo Polar - Gómez de Ágreda, Ángel (2014)
Climate change is a global phenomenon the effects of which will be felt in different ways in every corner of the planet. Numerous papers and studies have described more or less the possible consequences of global warming at local level. However, changes which take place in such a specific environment as the Arctic will also reverberate well beyond the Polar Arctic Circle. The navigability of polar routes, for instance, could allow access to the ample and rich tracts of land of Siberia through river systems heretofore obstructed by ice. In order to grasp the true scope of changes ahead it is necessary to conduct a dynamic study of all the factors involved. A sequential view of local scenarios will not suffice. In any event, we will have to get used to a more spherical and less cylindrical view of the world, which alienates the Polar Regions by regarding them as impassable. El cambio climático es un fenómeno global cuyos efectos se dejarán sentir de forma distinta en cada rincón del Planeta. Numerosos estudios han acometido la tarea de describir cuáles pueden ser las consecuencias más o menos locales del calentamiento global. Sin embargo, los cambios que acontezcan a nivel de un entorno tan concreto como el ártico también tendrán repercusiones más allá del Círculo Polar. La navegabilidad de las rutas polares, por ejemplo, podría permitir el acceso a las amplias y ricas extensiones de Siberia a través de vías fluviales hasta ahora taponadas. Para poder comprender el alcance de los cambios que se avecinan, es necesario hacer un estudio dinámico de todos los factores afectados, sin quedarse en la visión secuencial de los escenarios locales. De algún modo, habrá que acostumbrarse a una visión más esférica de la Tierra, en lugar de la cilíndrica que obvia las regiones polares por intransitables.